AN IMPORTANT BRANCH OF THE GREAT SILK ROAD THROUGH CENTRAL ASIA - Majidov Akbar Fayzullayevich (Journals Park Publishing, 2022)
This article contains the author's thoughts and comments on the fact that the Jizzakh oasis has been one of the cradles of ancient civilization and culture, its favorable geographical location and nature, the role of the Great Silk Road in the socio-economic life of the population
Keywords: Ustrushona; Khorezm; Bactria